Role of the neural pathway from hindbrain to hypothalamus in the regulation of energy homeostasis in rats. (12th February 2016) - Utoyama, Maiko; Akieda-Asai, Sayaka; Koda, Shuichi; Nunoi, Hiroyuki; Date, Yukari
Highlights: Food intake and body weight increased in rats with a midbrain transection. The midbrain-transected rats showed insulin resistance and hyperleptinemia. Hypothalamic POMC and CART decreased in the midbrain-transected rats. Abstract: Recent evidence suggests that neural pathways from the hindbrain to the hypothalamus are important for informing the hypothalamus of the body's condition with regard to energy metabolism. Here we examined energy metabolism in rats with transections of the midbrain that severed the neural pathway from the hindbrain to the hypothalamus, and then investigated the levels of various molecules associated with control of energy metabolism in these rats. Food intake and body weight were higher in the midbrain-transected rats than in sham-operated rats. In addition, the midbrain-transected rats showed insulin resistance and hyperleptinemia. Furthermore, the hypothalamic mRNA levels of anorectic proopiomelanocortin and cocaine- and amphetamine-related transcript were significantly lower in midbrain-transected rats than in sham-operated rats. Our findings elucidate the mechanisms of food intake and energy balance from the perspective of multifactorial regulatory systems that underlie functions such as neurohormonal integration.